Effect of Crack Orientation and Residual Stress on Stress Intensity Factors of Butt-Welded Steel Joints - Eman Elshrief; Abla El-Megharbel; Aly eldomiaty; Hassan abdelhafez (Port Said Engineering Research Journal, 2021)
Assessing the structural integrity of a cracked weldment is crucial. Cracks detected during welding inspections must be examined in the context of the structure's mechanical resistance. Generally, fracture mechanics supplies essential tools to determine a fracture criterion for loading conditions. This study explores the effect of residual stress (RS) and crack orientation on determining the stress intensity factor (𝐾 ) for a welded joint using the extended finite element method. This study comprises a 3D thermo-mechanical finite element (FE) analysis to study the temperature history and the residual stress distribution of a welded joint, and a 3D FE crack model that considers two cases of cracks—longitudinal (case I) and transverse (case II)—to calculate the 𝐾 value at the middle surface of a thin butt joint. 𝐾 is calculated for cracks under applied external and residual stresses. The results demonstrate that the welding residual stress can beneficially or detrimentally affect 𝐾 depending on stress distribution and sign, and indicate the significance of RS and crack orientation on 𝐾 . Simulation results demonstrate that the longitudinal crack in case I has higher 𝐾 values than those in case II for the transverse crack and show good agreement with the analytical results.